IO-Link Master Bridge - Matoušek, David; Černý, Ondřej (IEEE (Institute of Electrical and Electronics Engineers), 2022)
This article describes the practical implementation of the IO-Link master bridge, which ensure an interface between IO-Link devices and a main controlling computer. The main effect of this implementation is a simple data acquisition system based on a microcontroller that enables an easy expansion of many connected IO-Link devices. Concerning universal usage, the communication between the IO-Link master bridge and the computer works on standard UART units. Main computer and IO-Link master bridges interconnection ensure optocouplers. Thus, this method guarantees galvanic isolation firstly and easy expansion by the open collector technique secondly.
IO-Link můstek
Keywords: IO-Link; IO-Link master; UART; microcontroller; IO-Link; IO-Link master; UART; mikrořadič